A comprehensive survey of massive‐MIMO based on 5G antennas. Issue 12 (22nd October 2022) - Senger, Suverna; Malik, Praveen Kumar
Abstract: The rapid increase in the innovation of fifth‐generation (5th G) technology is a critical indicator of an explosion in technologies that satisfy everyday needs, and antennas for 5G with reduced delay, minimal path loss, and a continuous pattern of radiation will be essential. The upcoming 5G Massive multiple inputs, multiple outputs (MIMO) antenna will improve the performance of future‐generation wireless communication systems. The primary advantages of 5G technologies are their greater transmission speeds, extremely high data rates, improved reliability, less latency, enhanced spectral efficiencies, and the possibility of connecting a greater number of wireless devices to the networks. The Massive MIMO antenna is one of the most anticipated 5G technologies, which boosts the capacity compared to a conventional MIMO antenna, increasing the spectral efficiency by 50 times. In this review article, we discussed mutual coupling and then techniques and how to reduce the coupling between antennas. The goal of this study is to look at the huge MIMO antennas from a number of different angles.